Free‐breathing slice‐interleaved myocardial T2 mapping with slice‐selective T2 magnetization preparation. Issue 2 (19th October 2015) - Basha, Tamer A.; Bellm, Steven; Roujol, Sébastien; Kato, Shingo; Nezafat, Reza
Abstract : Purpose: To develop and evaluate a free‐breathing slice‐interleaved T2 mapping sequence by proposing a new slice‐selective T2 magnetization preparation (T2 prep) sequence that allows interleaved data acquisition for different slices in subsequent heartbeats. Methods: We developed a slice‐selective T2 prep for myocardial T2 mapping by adding slice‐selective gradients to a conventional single‐slice T2 prep sequence. In this sequence, five slices are acquired during five consecutive heartbeats, each using a slice‐selective T2 prep. The scheme was repeated four times using different T2 prep echo times. We compared the performance of the proposed slice‐interleaved T2 mapping sequence and the conventional single‐slice T2 mapping sequence in term of accuracy, precision, and reproducibility using phantom experiments and in vivo imaging in 10 healthy subjects. We also evaluated the feasibility of the proposed sequence in 28 patients with cardiovascular disease, and the quality of the maps was scored subjectively. Furthermore, we investigated the impact of through‐plane motion by comparing T2 measurements acquired during end‐systole versus mid‐diastole. Results: T2 measurements using a slice‐interleaved T2 mapping sequence were correlated with a spin echo (r 2  = 0.88) and single‐slice T2 mapping sequence (r 2  = 0.98). The mean myocardial T2 values were correlated between slice‐interleaved (48 ms) and single‐slice (51 ms) T2 mapping sequences. Subjective scores of T2 map quality were good to excellent in 81% of the maps in patients. There was no difference in T2 measurements between end‐systole versus mid‐diastole. Conclusions: The proposed free‐breathing slice‐interleaved T2 mapping sequence allows T2 measurements of five left ventricular slices in 20 heartbeats with similar reproducibility and precision as the single‐slice T2 mapping sequence but with a four‐fold reduction in acquisition time. Magn Reson Med 76:555–565, 2016. © 2015 Wiley Periodicals, Inc.